Symposium 5: Constellations of Collaboration: The Hidden Foundations of a Successful e-Learning Project - Courtney, Kathy (Proceedings of the International Conference on Networked Learning, 2004)
This paper describes and compares two developmental projects at Coventry University through stories told by individuals who were involved in the projects or had a close interest in them. Through these stories, and in some cases through interviews, the author seeks to gain a ‘composite’ picture of these developments and an understanding of how they interface with and relate to the University as a whole. Both projects can be regarded as having been highly successful. However, only one of them succeeded in producing a ‘ripple’ effect of new projects and further developments, involving other groups of staff. The paper seeks to identify some of the reasons which account for these differences in bringing about effective institutional change.